2004
DOI: 10.2166/wst.2004.0796
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of nitrifying granules observed in an aerobic upflow fluidized bed (AUFB) reactor

Abstract: The influences of trace metals in the wastewater and shear stress by aeration were particularly examined to clarify the formation mechanism of nitrifying granules in an aerobic upflow fluidized bed (AUFB) reactor. It was found that Fe added as a trace element to the inorganic wastewater accumulated at the central part of the nitrifying granules. Another result obtained was that suitable shear stress by moderate aeration (0.07-0.20 L/min/L-bed) promoted granulation. Furthermore, it was successfully demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…This has also been reported in other case studies on anaerobic and aerobic granules (2,13,29,37). Different layers were sometimes composed of distinct bacterial species with various functional tasks, such as nitrification, denitrification, or ammonia oxidation (1,4,38). In this study on aerobic granules, different structured zones could be identified as well.…”
Section: Downloaded Fromsupporting
confidence: 84%
“…This has also been reported in other case studies on anaerobic and aerobic granules (2,13,29,37). Different layers were sometimes composed of distinct bacterial species with various functional tasks, such as nitrification, denitrification, or ammonia oxidation (1,4,38). In this study on aerobic granules, different structured zones could be identified as well.…”
Section: Downloaded Fromsupporting
confidence: 84%
“…Therefore, there is a need for a simple yet effective method of immobilizing nitrifying bacteria within a reactor. Nitrifying granule production is one method of immobilization used to preserve a large population of nitrifying bacteria within a reactor (12,(40)(41)(42)(43). Tsuneda et al (41) produced nitrifying granules in inorganic wastewater using an aerobic upflow fluidized bed (AUFB) reactor.…”
mentioning
confidence: 99%
“…By means of energy dispersive X-ray spectroscopy, it has been found that Fe accumulated at the core of nitrifying granules. 7 On the other hand, it was reported that a shorter settling time accumulated more phosphorous and thus increased the ash solids fraction. However, the other poly-valence cations, i.e.…”
Section: Introductionmentioning
confidence: 99%